The value of ?-SMA in the evaluation of hepatic fibrosis severity in hepatitis B infection and cirrhosis development: a histopathological and immunohistochemical study - Akpolat, N; Yahsi, S; Godekmerdan, A; Yalniz, M; Demirbag, K (Wiley, 2005)
Aims: To investigate the value of alpha-smooth muscle actin (alpha-SMA), an indicator of stellate cell activation, in predicting fibrosis in chronic hepatitis B (CHB) patients. Methods and results: The liver biopsy specimens of 30 patients with a clinical diagnosis of CHB were obtained before treatment and scored by Knodell's histological activity index. The specimens were then immunohistochemically stained with alpha-SMA and semiquantitatively evaluated. Fibrosis and the immunoreactivity of alpha-SMA in the periportal, perisinusoidal and pericentral areas were compared. Fibrosis and necroinflammatory activity in CHB patients were significantly correlated (P =0.022). Furthermore, the degree of alpha-SMA expression and the scores of fibrosis (in periportal, perisinusoidal and pericentral areas) were highly correlated (P =0.000, 0.001, 0.000, respectively). Conclusions: In liver biopsy samples, alpha-SMA may prove to be a valuable marker in the evaluation of stellate cell activation and fibrosis progression and an early indicator of the development of fibrosis.
Keywords: alpha-smooth muscle actin; chronic hepatitis B; fibrosis; stellate cell